Physiological aspects and energetic contribution in 20s:10s high-intensity interval exercise at different intensities - Protzen, G. V.; Bartel, C.; Coswig, V. S.; Gentil, P.; Del Vecchio, F. B. (PeerJ, 2020)
Background: One of the most popular high-intensity interval exercises is the called "Tabata Protocol". However, most investigations have limitations in describing the work intensity, and this fact appears to be due to the protocol unfeasibility. Furthermore, the physiological demands and energetic contribution during this kind of exercise remain unclear.